2009
DOI: 10.1523/jneurosci.3018-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cortical Axon Elongation by a GABA-Driven Ca2+/Calmodulin-Dependent Protein Kinase Cascade

Abstract: Ca2ϩ signaling plays important roles during both axonal and dendritic growth. Yet whether and how Ca 2ϩ rises may trigger and contribute to the development of long-range cortical connections remains mostly unknown. Here, we demonstrate that two separate limbs of the Ca 2ϩ /calmodulin-dependent protein kinase kinase (CaMKK)-CaMKI cascades, CaMKK-CaMKI␣ and CaMKK-CaMKI␥, critically coordinate axonal and dendritic morphogenesis of cortical neurons, respectively. The axon-specific morphological phenotype required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
106
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 45 publications
1
106
0
Order By: Relevance
“…Nevertheless, intracellular systems that regulate individual arbor terminals in the axon have not been fully demonstrated. Ca 2+ is a major intracellular signaling molecule that regulates axonal growth (Kater and Mills, 1991;Gomez and Spitzer, 1999;Tang and Kalil, 2005;Ageta-Ishihara et al, 2009). Previous studies have suggested that localized Ca 2+ transients in restricted areas in the arbor enhance axonal growth, accompanied by retraction of other terminals (Hutchins and Kalil, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, intracellular systems that regulate individual arbor terminals in the axon have not been fully demonstrated. Ca 2+ is a major intracellular signaling molecule that regulates axonal growth (Kater and Mills, 1991;Gomez and Spitzer, 1999;Tang and Kalil, 2005;Ageta-Ishihara et al, 2009). Previous studies have suggested that localized Ca 2+ transients in restricted areas in the arbor enhance axonal growth, accompanied by retraction of other terminals (Hutchins and Kalil, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CaMKK/CaMK signaling cascades are regulated at multiple levels by Ca 2ϩ /CaM. CaMKK␣ and CaMKK␤ are expressed most abundantly in the brain (2), where CaMKK/CaMK signaling cascades play important roles in a number of physiologically important neuronal processes, including learning and memory (8,9), neuronal differentiation and migration (10), neurite outgrowth (11)(12)(13), and synaptogenesis (14). In addition, CaMKK␤, but not CaMKK␣, is an upstream activator of the AMP-dependent protein kinase (AMPK) (15)(16)(17).…”
mentioning
confidence: 99%
“…Using an elegant series of genetic studies, including knockdown, knock-out, and overexpression studies, the authors established that CaMKK activation of CaMKI␣ leads to axonal growth, whereas CaMKK activation of CaMKI␥ promotes dendritic outgrowth [Ageta-Ishihara et al (2009), their Fig. 1, Fig.…”
mentioning
confidence: 99%
“…This work provides clear evidence for a switch in CaMKKCaMKI signaling to control either dendritic or axonal elongation. Figure 1 provides a simple summary of the CaMKK-CAMKI signaling pathways derived from TakemotoKimura et al (2007) and Ageta-Ishihara et al (2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation